Formulation of Small Activating RNA Into Lipidoid Nanoparticles Inhibits Xenograft Prostate Tumor Growth by Inducing p21 Expression - Robert F Place; Ji Wang; Emily J Noonan; Rachel Meyers; Muthiah Manoharan; Klaus Charisse; Rick Duncan; Vera Huang; Xiaoling Wang; Long-Cheng Li (Elsevier, 2012)
Application of RNA interference (RNAi) in the clinic has improved with the development of novel delivery reagents (e.g., lipidoids). Although RNAi promises a therapeutic approach at silencing gene expression, practical methods for enhancing gene production still remain a challenge. Previously, we reported that double-stranded RNA (dsRNA) can activate gene expression by targeting promoter sequence in a phenomenon termed RNA activation (RNAa). In the present study, we investigate the therapeutic potential of RNAa in prostate cancer xenografts by using lipidoid-based formulation to facilitate in vivo delivery. We identify a strong activator of gene expression by screening several dsRNAs targeting the promoter of tumor suppressor p21WAF1/ Cip1 (p21). Chemical modification is subsequently implemented to improve the medicinal properties of the candidate duplex. Lipidoid-encapsulated nanoparticle (LNP) formulation is validated as a delivery vehicle to mediate p21 induction and inhibit growth of prostate tumor xenografts grown in nude mice following intratumoral injection. We provide insight into the stepwise creation and analysis of a putative RNAa-based therapeutic with antitumor activity. Our results provide proof-of-principle that RNAa in conjunction with lipidioids may represent a novel approach for stimulating gene expression in vivo to treat disease.